2016
DOI: 10.1183/13993003.00154-2016
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of diagnosed α1-antitrypsin deficiency and its comorbidities: results from a large population-based database

Abstract: α-Antitrypsin deficiency (AATD) is a genetically determined disorder that is associated with different clinical manifestations. We aimed to assess the prevalence of diagnosed AATD and its comorbidities using a large healthcare database.In this retrospective longitudinal observational study, we analysed data from 4 million insurants. Using International Classification of Diseases revision 10 (ICD-10) codes, we assessed the prevalence, comorbidities and healthcare utilisation of AATD patients (E88.0 repeatedly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 66 publications
5
63
2
2
Order By: Relevance
“…Genetic and biochemical studies of the HNF4A gene and protein in humans have suggested a broader role for HNF‐4α in the hepatic and pancreatic regulation of glucose homeostasis and have linked HNF‐4α to the development of the common late‐onset forms of type 2 diabetes . Interestingly, using a large health care database, patients with AATD were found to have a higher prevalence of diabetes compared to controls …”
Section: Discussionmentioning
confidence: 99%
“…Genetic and biochemical studies of the HNF4A gene and protein in humans have suggested a broader role for HNF‐4α in the hepatic and pancreatic regulation of glucose homeostasis and have linked HNF‐4α to the development of the common late‐onset forms of type 2 diabetes . Interestingly, using a large health care database, patients with AATD were found to have a higher prevalence of diabetes compared to controls …”
Section: Discussionmentioning
confidence: 99%
“…Compared with an age-and gender-matched reference population, AATD patients were found to have significantly more comorbidities, including arterial hypertension, congestive heart failure, ischaemic heart disease, chronic kidney disease, depression, diabetes, osteoporosis, gastroesophageal reflux disease and lung cancer (all p < 0.001), although the analysis incorporated a degree of selection bias as AATD testing was performed in patients already with disease (11). Patients with AATD typically have a more severe clinical course compared to those with other obstructive lung diseases, as evidenced by the significantly higher frequency of annual outpatient consultations and hospitalisations (Figure 3) observed in AATD patients compared to those with COPD, emphysema and asthma (11).…”
Section: Differentiating Aatd and Copdmentioning
confidence: 92%
“…Approximately 20,000 individuals with AATD were identified, inclusive of homozygous and heterozygous genotypes. To verify the internal validity of these estimates, we then investigated the prevalence of conditions known to be associated with AATD (vasculitis, chronic hepatitis, liver cirrhosis and panniculitis) among patients with AATD (ICD code E88.0) or COPD (11). Chronic hepatitis and cirrhosis were significantly more prevalent in patients with AATD than in those with COPD.…”
Section: Differentiating Aatd and Copdmentioning
confidence: 99%
“…Non-smoking COPD or COPD associated with minimal smoking is recognised, but should nevertheless prompt the consideration of other diagnoses (4 What about AATD? AATD may be associated with the onset of COPD at a young age and with more severe COPD relative to the amount smoked (2).…”
Section: Case Studymentioning
confidence: 99%
“…r AATD is a genetic disorder that causes defective production of alpha-1-antitrypsin (AAT), leading to decreased AAT activity in the blood and lungs and deposition of excessive abnormal AAT protein in liver cells (2). AATD is a laboratory diagnosis.…”
Section: Management Of Chronic Airway Diseases: What Can We Learn Fromentioning
confidence: 99%